Silver nanoparticle synthesis, characterization, properties - Bayazid, G.M. Asik; Shamma, Shahla Samim; Razy, Alim Al; Bosu, Rajib (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.